A Clinico-Pathological Study On Prameha Purvarupa (Pre- Diabetic Condition) And Its Management With Nisha-Amalaki Churna And Shilajeet Vati - Dhiman, Esha; Panda, Pradip Kumar; Singh, Vinod Chandra (International Research Journal of Ayurveda & Yoga, 2021)
Introduction- Purvarupa (Prodromal symptoms) of Prameha (Diabetes) helps in early diagnosis as well as prevention of the disease as compared to Rupa of Prameha. Purvarupa Avastha of Prameha is a condition in which the patients have high blood glucose but not up to the mark that can be defined as Diabetes Mellitus or Madhumeha. Materials and methods- 30 patients of Group A- (15 patients) and Group B- (15 patients) were registered from OPD and IPD of Govt. Ayurvedic College & Hospital, Balangir, presented with Subjective Parameter as Prabhuta mutrata (frequency of micturition), Pipasa (increased thirst), Kshudha (excessive appetite), Kara pada Daha (burning sensation in hand and feet), Kara-pada Suptata (numbness of hand and feet), Sweda Pravritti (excessive sweating), Mukha Shosha (dry mouth), Mukha Madhurya (sweetness in mouth), Sheeta Priyata (liking for cold things) and Madhura Shukla Mutrata (sweetness in urine) and Objective Parameter as fasting plasma glucose 100-125 mg%, oral glucose tolerance 140-200mg%, HbA1c 5.7%-6.4%. After diagnosis they were under trial with Ayurvedic formulations of Nisha-Amalaki Churna given 3gm twice daily empty stomach in Group A and Shilajeet Vati given 1 vati (500mg) twice daily empty stomach, for a period of 30 days with Ushna Jala respectively. The assessment of subjective and objective parameters were evaluated in 10th, 20th and 30th day from the day of initiation of trial up to 30 days in order to find the efficacy of both the trials by statistical paired ‘t’ test. Observation and results:- It has been observed that both the trial drugs revealed good result but drug of Group-A patients was highly significant (p<0.001) to reduce both Subjective and Objective parameter as compared to Group-B patients after 30 days of treatment. Discussion and Conclusion- Prameha (Diabetes) is a Kapha Pradhana Tridoshaja vyadhi in which Meda (Fat) is a Pradhan Dushya. Both the drugs had improved by reducing Prameha Purvarupa and the levels of FBS, PPBS and HbA1c in patients but Nisha-Amalaki Churna inferred better result as compare to Shilajeet Vati. No side effect was noticed during clinical study of Nisha-Amalaki Churna and Shilajeet Vati